Bilingual Education in Teaching English as A Foreign Language (EFL) in Indonesian University - Jalaluddin (Yayasan Sinergi Kawula Muda, 2023)
This paper concludes that the bilingual approach for teaching English in Indonesian universities is most effective, and the content and language integrated learning (CLIL) approach is particularly suitable. CLIL offers benefits such as the use of the first language to aid comprehension and identification of target language forms, connections to learners' previous knowledge, and improvements in self-confidence and motivation. Focused-form instruction (FFI) can be included in CLIL, which encourages attention to both meaning and language. The CLIL approach is therefore recommended for maximizing teaching effectiveness and learner benefits in the Indonesian university context.